Lincoln and race - Striner, Richard, 1950- (Concise Lincoln library., 2012)
"Abraham Lincoln is known as the Great Emancipator, yet his personal views on race have long been debated. Since his death, his legend has been shadowed by the mystery of his true stance toward non-whites. While Lincoln took many actions to fight slavery throughout his political career, his famously crafted speeches can be interpreted in different ways: at times his words suggest personal bigotry, but at other times he sounds like an enemy of racists. In Lincoln and Race, Richard Striner takes on one of the most sensitive subjects of Abraham Lincoln's legacy, exploring in depth Lincoln's mixed record and writings on the issue of race. Striner gives fair hearing to two prevailing theories about Lincoln's seemingly contradictory words and actions: Did Lincoln fight a long-term struggle to overcome his personal racism? Or were his racist comments a calculated act of political deception? Beginning with an exploration of the historical context of Lincoln's attitudes toward race in the years before his presidency, Striner details the ambiguity surrounding the politician's participation in the Free Soil Movement and his fight to keep slavery from expanding into the West. He explores Lincoln's espousal of colonization--the controversial idea that freed slaves should be resettled in a foreign land--as a voluntary measure for black people who found the prospect attractive. The author analyzes some of Lincoln's most racially charged speeches and details Lincoln's presidential words and policies on race and the hotbed issue of voting rights for African Americans during the last years of the president's life. A brief but comprehensive look into one of the most contentious quandaries about Abraham Lincoln, Lincoln and Race invites readers to delve into the mind, heart, and motives of one of America's most fascinating and complex leaders."--Project Muse.